2014
DOI: 10.1186/2054-9369-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on combat trauma treatment in cold regions

Abstract: Cold regions are a special combat environment in which low temperatures have a great impact on human metabolism and other vital functions, including the nervous, motion, cardiovascular, circulatory, respiratory, and urinary systems; consequently, low temperatures often aggravate existing trauma, leading to high mortality rates if rapid and appropriate treatment is not provided. Hypothermia is an independent risk factor of fatality following combat trauma; therefore, proactive preventative measures are needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…With all these considerations in mind, it is important to remember that managing a hemorrhagic combat casualty in a cold environment involves more than just keeping blood products warm. 28,29 Maintaining the patient's body temperature is crucial to prevent hypothermia, a key part of the lethal triad, which significantly increases mortality risk. [30][31][32][33] Additionally, using tactical hemostatic materials can be challenging due to technical winter clothing, and the mental and physical strain on medical personnel in these conditions is substantial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With all these considerations in mind, it is important to remember that managing a hemorrhagic combat casualty in a cold environment involves more than just keeping blood products warm. 28,29 Maintaining the patient's body temperature is crucial to prevent hypothermia, a key part of the lethal triad, which significantly increases mortality risk. [30][31][32][33] Additionally, using tactical hemostatic materials can be challenging due to technical winter clothing, and the mental and physical strain on medical personnel in these conditions is substantial.…”
Section: Discussionmentioning
confidence: 99%
“…With all these considerations in mind, it is important to remember that managing a hemorrhagic combat casualty in a cold environment involves more than just keeping blood products warm 28,29 . Maintaining the patient's body temperature is crucial to prevent hypothermia, a key part of the lethal triad, which significantly increases mortality risk 30–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional resuscitation strategies for the treatment of exsanguinating traumatic cardiac arrest are poor. Furthermore, when trauma occurs in colder regions, the effect of treatment is lessened [ 1 ]. Although some traumatic injuries can be surgically treated [ 2 ], more than half of the trauma patients in recent military conflicts died because of limited medical care [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia induces vascular endothelial growth factor (VEGF) gene transcription in human osteoblast-like cells through HIF-2α [ 3 ]. Hypoxia induced by fracture significantly upregulates the expression of bone morphogenetic protein 2 (BMP-2), an osteogenic cytokine at the fracture site, in the capillary endothelial cells [ 4 , 5 ]. It is also suggested that endothelial cells may play a role in stimulating MC3T3 cells through the potent osteogenic factor BMP-2, other than in promoting angiogenesis.…”
Section: Introductionmentioning
confidence: 99%